2020
DOI: 10.1101/2020.12.13.422360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

5-HT2Creceptor perturbation has bidirectional influence over instrumental vigour and restraint

Abstract: The serotonin (5-HT) system, particularly the 5-HT2C receptor, has consistently been implicated in behavioural control. However, while some studies have focused on the role 5HT2C receptors plays in regulating motivation to work for reward, others have highlighted its importance in response restraint. To date, it is unclear how 5-HT transmission at this receptor regulates the balance of response invigoration and restraint in anticipation of future reward. In addition, it remains to be established how 5HT2C rece… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(178 reference statements)
1
0
0
Order By: Relevance
“…This demonstrates that although activity at D1Rs can promote cue-driven decisions to act, it is not necessary for actions to be executed. Finally, we have reported that intra-NAcC administration of the stimulant amphetamine causes a much broader range of premature responses than observed in the current study, with increases in impulsive actions observed not only throughout the early and late intervals of the No-Go holding period but also in the pre-cue period (Harmson, Grima, Panayi, Husain, & Walton, 2020).…”
Section: Discussionsupporting
confidence: 46%
“…This demonstrates that although activity at D1Rs can promote cue-driven decisions to act, it is not necessary for actions to be executed. Finally, we have reported that intra-NAcC administration of the stimulant amphetamine causes a much broader range of premature responses than observed in the current study, with increases in impulsive actions observed not only throughout the early and late intervals of the No-Go holding period but also in the pre-cue period (Harmson, Grima, Panayi, Husain, & Walton, 2020).…”
Section: Discussionsupporting
confidence: 46%